2022
DOI: 10.1177/15330338221119748
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Benign and Malignant Pulmonary Ground-Glass Nodules Using Computed Tomography Radiomics Parameters

Abstract: Objective: To assess the clinical value of a radiomics model based on low-dose computed tomography (LDCT) in diagnosing benign and malignant pulmonary ground-glass nodules. Methods: A retrospective analysis was performed on 274 patients who underwent LDCT scanning with the identification of pulmonary ground-glass nodules from January 2018 to March 2021. All patients had complete clinical and pathological data. The cases were randomly divided into 191 cases in a training set and 83 cases in a validation set usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Beyond the first-order histogram features, the second-and higher-order texture features extracted by radiomics techniques were also integrated in the assessment of invasiveness among SSNs (30)(31)(32). Li et al obtained the CT texture features of 109 SSNs and found that the surface area feature and the extruded surface area feature could be predictors of IACs compared with MIAs (33).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the first-order histogram features, the second-and higher-order texture features extracted by radiomics techniques were also integrated in the assessment of invasiveness among SSNs (30)(31)(32). Li et al obtained the CT texture features of 109 SSNs and found that the surface area feature and the extruded surface area feature could be predictors of IACs compared with MIAs (33).…”
Section: Discussionmentioning
confidence: 99%